Total Neoadjuvant Therapy in Rectal Cancer: A Systematic Review and Meta-analysis of Treatment Outcomes. Issue 3 (March 2020) - Petrelli, Fausto; Trevisan, Francesca; Cabiddu, Mary; Sgroi, Giovanni; Bruschieri, Lorenza; Rausa, Emanuele; Ghidini, Michele; Turati, Luca
Abstract : Background: The addition of induction chemotherapy to concomitant neoadjuvant chemoradiation in locally advanced rectal cancer could increase pathological downstaging and act on occult micrometastatic disease, leading ultimately to a better outcome. A systematic review was carried out of the existing literature on the treatment outcomes of total neoadjuvant therapy (TNT) on locally advanced rectal cancer. TNT was defined as chemotherapy using cycles of induction and/or consolidation in conjunction with standard chemoradiotherapy prior to surgery. Methods: A systematic search of PubMed, Embase, and the Cochrane Library was performed according to the PRISMA statement up until January 2019. The primary endpoints were complete pathologic response (pCR), disease-free survival, and overall survival rates. Results: A total of 28 studies (3 retrospective and 25 prospective for a total of 3579 patients) were included in the final analysis (n = 2688 treated with TNT and n = 891 with neoadjuvant chemoradiotherapy therapy). The pooled pCR rate was 22.4% (95% CI 19.4%–25.7%) in all patients treated with TNT (n = 27 studies with data available). In n = 10 comparative studies with data available, TNT was found to increase the odds of pCR by 39% (1.40, 95% CI 1.08–1.81, P = 0.01). Conclusions: The addition of induction or consolidation chemotherapy to standard neoadjuvant chemoradiotherapy results in a higher pCR rate. Given that the comparative analysis was derived from few randomized publications, large confirmatory trials should be carried out before a strong recommendation is made in favor of TNT.